Fundamentals of nursing : standard & practice - DeLaune, Sue C. [ (Sue Carter)] (Dalmer Cengage Learning, 2011)
Rev. ed. of: Fundamentals of nursing / [edited by] Sue C. DeLaune, Patricia K. Ladner. 2002